2002
DOI: 10.1177/104365960201300105
|View full text |Cite
|
Sign up to set email alerts
|

Daily Living Practice of the Life-Satisfied Thai Elderly

Abstract: The purpose of this study was to determine whether the life satisfaction of Thai elderly depends on their daily living practice. A comparative design was used to study 73 matched pairs of elderly people who perceive themselves as life satisfied or life dissatisfied. Scores of 85% and above on the life satisfaction instrument were used as a criteria to identify the elderly with life satisfaction. The sample was drawn from elderly clubs in four provinces of the eastern border of Thailand. Data were collected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…However, in suburban and urban areas, religion and family relationships were not a strong concern because of new invading international culture. Matsubayashi et al (1992) and Othaganont, Sinthuvorakan, and Jensupakarn (2002) found that religious activities and a good relationship with others, including family members, are important in determining life satisfaction and feeling good in the elderly. Knodel et al's study (1987, as cited in Gray & Kramanon, 2007 indicated that the Buddhist religion has been considered an important aspect of the Thai people, as it influences their attitudes, thoughts and way of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in suburban and urban areas, religion and family relationships were not a strong concern because of new invading international culture. Matsubayashi et al (1992) and Othaganont, Sinthuvorakan, and Jensupakarn (2002) found that religious activities and a good relationship with others, including family members, are important in determining life satisfaction and feeling good in the elderly. Knodel et al's study (1987, as cited in Gray & Kramanon, 2007 indicated that the Buddhist religion has been considered an important aspect of the Thai people, as it influences their attitudes, thoughts and way of life.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Othaganont, Sinthuvorakan, and Jensupakarn (2002) indicated that well-planned use of income contributes to life satisfaction of Thai elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Thai elderly report religious beliefs, children, and contributing in a meaningful way to the community as important to life satisfaction (Othaganont, Sinthuvorakan, & Jensupakarn, 2002). Conversely, difficult family relationships are described as one of the major reasons for depression in Thai elders.…”
Section: Background To the Studymentioning
confidence: 98%
“…The global pattern of ageing populations is accelerated in Thailand, as with other Asian countries, as a consequence of a rapid increase in longevity due to recent economic and social developments, followed by a sharp fall in the birth rate (Lau, Chi, & McKenna, 1998;Limanonda). Over the last two decades the average life expectancy for females increased from 65 to 75 years (Chirawatkul, Patanasri, & Koochaiyasit, 2002;Othaganont, Sinthuvorakan, & Jensupakarn, 2002). Households in the north of Thailand have a robust matrilineal tradition with kinship and family ancestry being established through the female line (Klausner, 1998;Kwong, 2000;Limanonda;Vichit-Vadakan, 1994).…”
Section: Background To the Studymentioning
confidence: 98%
“…[26]. The findings suggest the importance of Thai elderly's good practice on food habits, regular exercise, seeking knowledge toward health, religious activity involvement, good relationships with others, and well-planned income and expenses resulting in life satisfaction [27]. Buraskorn et al suggested "clubs for the elderly" as effective in improving "purpose of life feeling" in Thailand [28].…”
Section: Factors That Influence the "Purpose Of Life" By Each Countrymentioning
confidence: 99%